The mediating role of child-teacher dependency in the association between early mother-child attachment and behavior problems in middle childhood. Issue 5 (3rd September 2021) - Neuhaus, Robin; McCormick, Meghan; O'Connor, Erin
ABSTRACT: This study examines child-teacher dependency in preschool as a pathway through which mother-child attachment is associated with children's behavior problems across middle childhood. Data include direct assessments of attachment security and styles, teacher reports of child-teacher dependency, and maternal reports of behavior problems from the NICHD SECCYD ( N = 769 children). Children with more secure attachments at 24 months were less likely to exhibit child-teacher dependency at 54 months. Children with ambivalent, controlling, or insecure/other attachments at 36 months had higher levels of child-teacher dependency at 54 months. Results from multi-level models showed that child-teacher dependency at 54 months was associated with higher levels of internalizing, but not externalizing, behavior problems across middle childhood. Child-teacher dependency partially mediated the association between insecure/other mother-child attachment and internalizing behaviors in middle childhood. Supporting preschool teachers to reduce child-teacher dependency may help ameliorate risk for internalizing behaviors posed by insecure/other attachment.